2019
DOI: 10.1021/acs.biomac.9b00367
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stable, Coordinated Polymeric Nanoparticles Loading Copper(II) Diethyldithiocarbamate for Combinational Chemo/Chemodynamic Therapy of Cancer

Abstract: Disulfiram (DSF) has excellent in vitro anticancer activity in the presence of Cu(II). The anticancer mechanism studies have demonstrated that copper(II) diethyldithiocarbamate, Cu(DDC) 2 , is the crucial DSF's metabolite exhibiting anticancer activity. In this paper, highly stable polymeric nanoparticles were fabricated via a coordination strategy between Cu(II) and carboxylic groups in poly(ethylene glycol)-b-poly(ester-carbonate) (PEC) for efficient loading of Cu(DDC) 2 , which was generated by the in situ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(62 citation statements)
references
References 44 publications
0
62
0
Order By: Relevance
“…Furthermore, the anti-cancer activity of DSF has been explored since 1977 ( 17 ). DSF is rapidly converted to diethyldithiocarbamate in the system, which forms a stable complex with Cu; the complex exhibits a stronger anti-tumor effect than DSF alone ( 18 ). DSF/Cu complex has been reported to suppress the growth and metastasis of non-small-cell lung cancer (NSCLC), hepatocellular carcinoma, and oral squamous cell carcinoma ( 6 , 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the anti-cancer activity of DSF has been explored since 1977 ( 17 ). DSF is rapidly converted to diethyldithiocarbamate in the system, which forms a stable complex with Cu; the complex exhibits a stronger anti-tumor effect than DSF alone ( 18 ). DSF/Cu complex has been reported to suppress the growth and metastasis of non-small-cell lung cancer (NSCLC), hepatocellular carcinoma, and oral squamous cell carcinoma ( 6 , 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…As this study was originally designed to explore the role of DSF/Cu in inhibiting the growth of GC cells, a positive control was not used; this is a limitation of the current study. Multiple studies have demonstrated that DSF-nanoparticles have enhanced anti-cancer effect ( 18 ). In the future, we plan to perform nano-modification of DSF and use docetaxel as a positive control to further explore the role of DSF in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The design of coordinated polymer nanoparticles with the encapsulation of Cu(II) diethyldithiocarbamate (Cu(DDC) 2 ) exhibited synergistic therapeutic outcome of chemotherapy and CDT, where Cu(DDC) 2 exerted the chemotherapeutic function and the additional bioavailable Cu(II) out of Cu(DDC) 2 catalyzed the production of hydroxyl radicals in oxidative tumor therapy. [202] The construction of Cu 2−x E-Au (E = S, Se) heteronanostructure concurrently achieved augmented attenuation Figure 22. Schematic illustration of the underlying synergistic therapeutic mechanism of copper(I) phosphide nanocrystals (CP NCs) for multimodality imaging-guided photothermal ablation and photothermal-enhanced CDT of the deep-seated tumor.…”
Section: Cu-involved Nanoagents For Synergistic Nanotherapeuticsmentioning
confidence: 99%
“…The design of coordinated polymer nanoparticles with the encapsulation of Cu(II) diethyldithiocarbamate (Cu(DDC) 2 ) exhibited synergistic therapeutic outcome of chemotherapy and CDT, where Cu(DDC) 2 exerted the chemotherapeutic function and the additional bioavailable Cu(II) out of Cu(DDC) 2 catalyzed the production of hydroxyl radicals in oxidative tumor therapy. [ 202 ]…”
Section: Cu‐involved Nanoagents For Synergistic Nanotherapeuticsmentioning
confidence: 99%
“…These characteristics explain their higher accumulation in human oral epithelial carcinoma vincristine-resistant tumors (KBV) that further improved the efficacy of tumor theranostics, such as those using chemotherapy and photothermal therapy [76]. The [Cu(ddc) 2 ] (13) moiety coordinated to carboxylic groups from poly(ethylene glycol)-b-poly(ester-carbonate) generated a highly stable system able to inhibit A549 cells proliferation both in vitro and in vivo [77]. The interest for this bacc is generated by the fact that dsf exhibits an excellent in vitro antiproliferative activity mediated by (13) as its metabolite.…”
Section: Polymeric Systemsmentioning
confidence: 99%